Characterisation of an extract and fractions of Azadirachta indica flower on cholesterol lowering property and intestinal motility. Issue 10 (19th May 2019) - Duangjai, Acharaporn; Nuengchamnong, Nitra; Lee, Learn-Han; Goh, Bey-Hing; Saokaew, Surasak; Suphrom, Nungruthai
Abstract: Azadirachta indica has long been used in traditional medicine. This study focused on isolation and characterisation of active ingredients in the extract, its fractions (NF-EA, NF-AQ, NF-G) and its effect on the cholesterol absorption activity. The NF-EA fraction was identified by marker compounds by LC-ESI-QTOF/MS. Cholesterol absorption activity was performed by measuring the solubility and size of cholesterol micelles. The intestinal motility was also examined by isolated rat's ileum to test the contraction. The extract and its fractions consist of flavonoids and phenolic compounds, like quercetin, kaempferol and myricetin. We found that A. indica extract and NF-EA increase cholesterol micelles size, while the extract, NF-AQ, myricetin and quercetin, reduced the solubility of cholesterol in micelles. The extract and quercetin inhibited the contraction induced by KCl up to 29 and 18%, respectively, and also decreased CaCl2 -induced contraction. This finding is in support to traditional uses of A. indica as cholesterol-lowering agents and regulator of gastrointestinal motility. Abstract :